ドームフジ ニ オケル ホウシャ カンソク - 平沢, 尚彦; ヒラサワ, ナオヒコ; 藤田, 耕史; フジタ, コウジ; Hirasawa, Naohiko; Fujita, Koji (2008)
P(論文) 第44次南極地域観測隊により,2003年2月1日から2004年1月20日の地上放射観測(短波上向き・下向き,長波上向き・下向き)の結果を報告する.放射計ドームの着霜を回避する目的でファン付き放射計を用いた上向き,下向きの長波放射,及び下向きの短波放射は1997年の観測値と比較的近い値を示し,両年の観測の妥当性を示唆した.しかし,ファンのない放射計を用いた上向き短波放射は,極夜前後の1-2カ月において下向き短波放射を上回るなど,異常値を示している.着霜がこの原因の候補の一つであるが,確かめられない.データの修正については今後の課題とする.また,極夜期の上向き・下向き長波放射について,典型的な地表面放射冷却時期と放射冷却が抑制される時期について,事例を示した. This paper reports radiation observations at Dome Fuji Station from February 1, 2003 to January 20, 2004, carried out by the 44th Japanese Antarctic Research Expedition team. The radiometers which measured the upward longwave radiation (LWu), the downward longwave (LWd) and the downward shortwave (SWd) were equipped with fans to avoid frosting on the surface of the radiometer dome by air circulation. The upward shortwave radiation (SWu) measured by a radiometer without fan needs correction, which we leave as a problem for the future. In addition, as for LWd and LWu in the polar night, a typical radiational cooling case and a suppressed radiational cooling one are shown. departmental bulletin paper